Seasonal variations in the structure of copepod assemblages in tropical marine and estuarine waters, Coleroon, South-East India - Rajkumar, Mayalagu; Sun, Jun; Jenkinson, I. R.; Rahman, Mohammad Mustafizur (Marine Biological Association of the United Kingdom, 2014)
A twelve-month investigation was undertaken on how copepod community structure varied in relation to environmental factors in the Coleroon estuary, south-east India. Sampling was monthly, from Station 1 in the sea to Station 4 in the Vettar backwaters. Canonical correspondence analysis (CCA) was applied to elucidate the environmental factors affecting the copepod community. A total of 104 copepod species in 38 genera and 26 families were recorded, with the Calanoids, Acartia erythraea and Oithona brevicornis being the most dominant. At all four stations, both these species loaded near the intercept of CCA axes 1 and 2, perhaps reflecting that they were autochthonous. Most species occurred in distinct seasonal patterns. Abundances ranged from 13 × 103 to 215 × 103 (ind. m-3). Coleroon waters showed high diversity (bits/ind.), from 5.29 at Station 3 to 4.97 at Station 4. Abundance correlated positively with temperature and salinity and negatively with rainfall, dissolved oxygen concentration (DO) and pH. Species diversity correlated strongly with abundance (P<0.01). Abundance and diversity were highest during the summer, and both correlated positively with salinity. Temperatures (air and water), salinity, pH and DO varied in the ranges 26–36oC,25–34.2oC, 9–38, 7.0–8.7 and 3.0–6.8 ml l-1, respectively. Nitrate, nitrite, phosphate and silicate (mM) varied in the ranges: 4.7–64.5, 0.4–14.1, 0.2–12.9 and 9.3–148, respectively.